(untitled) (Italian Review of Legal History, 2021)
A little-known story relating to a season of trade union struggles is the one in which the jasmine flower pickers of Ionian Calabria were the protagonists. Their work represented, between the fifties and the seventies of the twentieth century, an important element in the economic and social history of the Calabrian territory, favoring the creation of an interesting network of connection between the numerous small and medium-sized agricultural companies operating in the territory and some of the best-known brands of the French perfume industry. The acquired awareness of the “international” profile and, therefore, of the importance of one’s work in the industrial and social promotion of the territory, was at the origin of a season of claims, which sanctioned a clear improvement in working conditions and greater social consideration for these women who suddenly found themselves, also as a result of male unemployment and emigration, to fill the role of head of the family; they also brought to the attention of Parliament the need to give regulatory recognition to the requests of female workers. In the trade union struggle conducted by these pioneers of the rights of female workers, at a certain point, interests intertwined that risked distorting the meaning, but they were able to cope with the exploitation that came from various sides, fighting only for their rights. The crisis in the sector, determined by an excess of production compared to the demand and by competition from some foreign countries (Egypt, Israel, Spain, Algeria, Tunisia), which could also benefit from lower labor costs, caused a vertical collapse in sales of jasmine, leading within a few years to the total disappearance of the crop from the Calabrian coasts. The legislator intervened belatedly to regulate many of those rights that the female jasmine pickers had managed to conquer, obtaining a provincial collective bargaining that respected and recalled customary law. State intervention was late because at the end of the seventies almost no one in Calabria was growing jasmine and the changed conditions of the international market diverted orders from French industry to more competitive countries. However, the pioneering role of these women, whose work in itself traced a gender identity, certainly marked a decisive step towards social change and women’s emancipation, which it seems necessary to remember.